(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research aims at identifying the impacts of Active learning on the achievement and acquisition of the fourth grade students in Subject science and health education, and their acquisition of some life skills : It formed the research sample consisted of (138) pupils distributors into two groups: the first trial included (77) male and female pupils, and the second control group included (61) male and female pupils,. The experimental group was taught using Active Learning strategies, while the control group followed the common used teaching methodology, and a life-skills scale was applied on both groups .Results shows a statically significant difference between the experimental and control groups in favor of the experimental group whether it is for the achievement test or the life-skills scale due to the different methodologies applied (Active Learning).